Export Competitiveness of Select Firms from India: Glimpse of Trends and Implications - Manthri, Pranusha; Bhokray, Ketan; Momaya, Kirankumar S. (Indian Journal of Marketing, 2015)
Competitiveness is becoming necessary for growth, balances, and sustainability of Indian firms. With the new government at the Centre, India seems keen to progress to next stages of competitiveness such as cooperation-driven or innovation-driven to boost employment, growth, and prosperity. Massive imports that accompany rapid growth are to be balanced with exports, an area of urgent catch-up by firms of Indian origin (FIOs). The paper used a database approach to identify differences in patterns of export performance of key firms in select polar industries using the concept of trade competitiveness index (TCI). While software players are visible giants, remarkable consistency in improvement was found in manufacturing also, and some exceptional firms were found in the auto sector. Considering the vast pool of Indian marketing and other professionals - some may be effective in international markets - the FIOs should try to balance trade through scale-up in exports. The concepts and levels highlighted in this paper may inspire other capable firms to aim high and build necessary capabilities to play the longer-term game of international competitiveness.